2022
DOI: 10.3390/sym14122529
|View full text |Cite
|
Sign up to set email alerts
|

Design of Chaotic Interleaver Based on Duffing Map for Turbo Code

Abstract: This article presents the performance analysis and comparison of turbo codes for several interleavers with short blockchains. According to the symmetry concept, turbo codes consist of two symmetric convolutional codes preceded by an interleaver. Some interleavers can be described by symmetric 3 × 3 generator matrices, whereas others are represented through symmetric matrices in which the nonzero terms in the matrix are monomials. Interest in short blockchains has grown over the years because of their use in em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The peculiarity of the proposed modification is not only in the selection of a more successful Duffing equation, which gives a more random distribution than the Lozi equation, for example, as in [11], as well as in the application of the analysis of the distance spectrum of the code and the condition of choosing a greater distance between elements by permutations by code words with a small by weight.…”
Section: Discussion Of Results Of Investigating the Modification Of T...mentioning
confidence: 99%
See 2 more Smart Citations
“…The peculiarity of the proposed modification is not only in the selection of a more successful Duffing equation, which gives a more random distribution than the Lozi equation, for example, as in [11], as well as in the application of the analysis of the distance spectrum of the code and the condition of choosing a greater distance between elements by permutations by code words with a small by weight.…”
Section: Discussion Of Results Of Investigating the Modification Of T...mentioning
confidence: 99%
“…We proposed using one of the Duffing equations in the chaotic interleaver instead of the Lozi equations, which also gives the chaotic distribution dynamics. Analyzing works with a chaotic interleaver based on the Duffing equations [11] and considering many other Duffing equations, several Duffing equations as part of turbo codes were considered and their characteristics were analyzed. They made it possible to obtain different minimum distances between elements.…”
Section: Y I B X I = ⋅ −mentioning
confidence: 99%
See 1 more Smart Citation
“…Sahnoune and Berkani concluded that, compared with a random interleaver and dithered Golden interleaver, a chaotic interleaver has low latency, low complexity of implementation, and improves the security of the encoded data. Urrea et al [54] compared the performances of a chaotic interleaver with short block lengths to a new chaotic interleaver based on the Duffing map, which showed slightly better performance.…”
mentioning
confidence: 99%